Powder for molded inductor and preparation method thereof

By passing the FeSiAl powder particles and coating the silica layer, the problems of unstable magnetic performance and poor corrosion resistance of traditional molded inductors under high frequency conditions are solved, and high frequency stability and high-efficiency magnetic permeability are achieved , meet high-end market demand.

CN119296905APending Publication Date: 2025-01-10SHENZHEN TOPSUN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411502602.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional molded inductors perform poorly under high-frequency conditions, unstable magnetic properties and poor corrosion resistance, which limits their application and equipment efficiency in high voltage and high current conditions.

Method used

By passing the FeSiAl powder particles, a phosphate passivation corrosion resistance layer is formed, and a silica layer cladding layer is grown on its surface to form a component transition zone to improve its corrosion resistance and magnetic properties.

Benefits of technology

It achieves stable performance and good corrosion resistance under high-frequency conditions, reduces magnetic losses, improves effective magnetic permeability and service life, and obtains high-reliability molded inductor powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102994150000071
    Figure BDA0005102994150000071
  • Figure BDA0005102994150000081
    Figure BDA0005102994150000081
Patent Text Reader

Abstract

The invention relates to the technical field of inductors, in particular to powder for a molded inductor and a preparation method of the powder. A preparation method of powder for a mould pressing inductor comprises the steps that firstly, clean FeSiAl powder particles are subjected to passivation treatment, a phosphate passivation corrosion-resistant layer is obtained, then a silicon dioxide coating layer grows on the surface of the phosphate passivation corrosion-resistant layer through an in-situ reaction, phosphoric acid is added into an in-situ reaction system, and the powder for the mould pressing inductor is obtained. A phosphate passivation corrosion-resistant layer and a silicon dioxide coating layer are coated on the FeSiAl powder, so that a component transition region is formed between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer, the coated FeSiAl powder has excellent corrosion resistance, and meanwhile, the FeSiAl powder has the advantages of small magnetic loss, high effective magnetic conductivity, stable performance and long service life; and moreover, the surface protection layer and the FeSiAl powder particles are subjected to coordinated deformation in the later external force deformation process, and the possibility of cracks or defects of the silicon dioxide layer is small, so that the high-reliability powder for the mold pressing inductor can be obtained, and the high-end market requirement can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inductors, and in particular to a powder material for molded inductors and a preparation method thereof. Background Art

[0002] With the rapid development of power electronics technology, high frequency has become one of the trends, which puts higher requirements on electromagnetic components, especially molded inductors used in low-voltage circuits. Molded inductors are widely used due to their compact structure and high reliability, but traditional molded inductors are sensitive to changes in the external environment, especially under high-frequency conditions, which is prone to large energy losses. This not only limits its application in high-voltage and high-current conditions, but also affects the overall efficiency of the equipment.

[0003] Most molded inductors on the market today are made from traditional ferrite materials or simple mixed metal powders. The former is cheaper, but performs poorly at high frequencies; the latter can alleviate the loss problem to a certain extent, but due to the lack of detailed component control and technical improvements, it still cannot fully achieve the ideal state. Both methods generally have problems such as unstable magnetic properties and poor corrosion resistance.

[0004] Therefore, it is necessary to develop a powder material for molded inductors that can maintain stable performance under high-frequency conditions and has good corrosion resistance to meet the needs of the high-end market. Summary of the invention

[0005] The purpose of the present application is to provide a powder material for molded inductors and a preparation method thereof in view of the deficiencies of the current technology. The powder material for molded inductors prepared in the present application is prepared by first passivating clean FeSiAl powder particles to obtain a phosphate passivation corrosion-resistant layer, and then growing a silicon dioxide coating layer on the surface of the phosphate passivation corrosion-resistant layer through an in-situ reaction. Phosphoric acid is added to the in-situ reaction system, so that there is a composition transition zone between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer, which not only ensures that the coated FeSiAl powder has excellent corrosion resistance, but also has small magnetic loss, high effective magnetic permeability, stable performance and long service life; and in the later deformation process caused by external force, the surface protective layer and the FeSiAl powder particles are deformed in coordination, and the possibility of cracks or defects in the silicon dioxide layer is small, thereby obtaining a high-reliability powder material for molded inductors to meet the needs of the high-end market.

[0006] In a first aspect, the present application provides a method for preparing powder for molded inductors, using the following technical solution: A method for preparing powder for molded inductors, comprising the following steps: S1, ultrasonically cleaning FeSiAl powder particles with an anhydrous ethanol solution, ultrasonically cleaning with deionized water, filtering the deionized water to obtain clean FeSiAl powder particles, and then passivating the clean FeSiAl powder particles to obtain passivated FeSiAl powder; S2. Preliminarily dissolving appropriate amounts of reaction precursors and phosphoric acid in a solvent according to their mass fractions to prepare a mixed solution for forming a surface coating layer; S3. According to the mass proportion, add 60 parts of passivated FeSiAl powder into 35 parts of pure water and stir evenly to obtain a mixed solution A. Then, drop 0.2-0.3 parts of a solution containing a catalyst into the mixed solution A, stir evenly, heat to 60-70°C, slowly add 75 parts of the prepared mixed solution, stir to react for 4-5 hours, and then let it stand for 18-20 hours to allow the reaction precursor to hydrolyze and condense on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating of silicon dioxide; then separate the solid and liquid, wash, and vacuum dry to obtain a powder for molded inductors.

[0007] By adopting the above technical scheme, step S1: ultrasonically clean the FeSiAl powder particles with anhydrous ethanol solution, then ultrasonically clean them with deionized water, filter out the deionized water, and obtain clean FeSiAl powder particles. Then, the clean FeSiAl powder particles are passivated to obtain FeSiAl powder after passivation. The purpose of this step is to remove impurities and oxides on the surface of the FeSiAl powder particles, improve their surface activity, and provide a good foundation for subsequent in-situ reactions. Step S2: According to the mass fractions, dissolve an appropriate amount of reaction precursor and phosphoric acid in a solvent in advance, and configure a mixed solution that will generate a surface coating layer. The purpose of this step is to prepare a precursor solution containing phosphate and silicon dioxide to provide raw materials for subsequent in-situ reactions. Step S3: According to the mass fractions, add 60 parts of passivated FeSiAl powder to 35 parts of pure water and stir evenly to obtain a mixed solution A. Then, 0.2-0.3 parts of the solution containing the catalyst is added dropwise to the mixed solution A, stirred evenly, heated to 60-70°C, and 75 parts of the prepared mixed solution are slowly added, stirred for reaction for 4-5 hours, and then allowed to stand for 18-20 hours. The reaction precursor is hydrolyzed and polycondensed on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating layer of silica. Then the solid and liquid are separated, washed, and vacuum dried to obtain a powder for molded inductors. The purpose of this step is to grow a silica coating layer on the surface of the phosphate passivation corrosion-resistant layer through an in-situ reaction to form a powder for molded inductors with excellent corrosion resistance, low magnetic loss, high effective magnetic permeability, stable performance, and long service life. There is a synergistic effect between the steps: First, the passivation treatment in step S1 can improve the surface activity of the FeSiAl powder particles, providing a good foundation for the subsequent in-situ reaction. Secondly, the dissolution of the reaction precursor and phosphoric acid in step S2 and the configuration of the mixed solution provide raw materials for the subsequent in-situ reaction. Finally, the in-situ reaction in step S3 creates a composition transition zone between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer, which not only ensures that the coated FeSiAl powder has excellent corrosion resistance, but also has the characteristics of low magnetic loss, high effective magnetic permeability, stable performance, and long service life. In addition, during the later deformation process caused by external forces, the surface protective layer and the FeSiAl powder particles are deformed in coordination, and the possibility of cracks or defects in the silicon dioxide layer is small, thereby obtaining high-reliability powder for molded inductors to meet the needs of the high-end market.

[0008] Preferably, in step S1, the average particle size of the FeSiAl powder particles is 5.0-20.0 μm.

[0009] Preferably, in step S1, during the cleaning process of the FeSiAl powder particles, anhydrous ethanol is used for ultrasonic cleaning for 30-70 minutes, and then deionized water is used for ultrasonic cleaning 4 times, each cleaning time is 3-5 minutes, the amount of anhydrous ethanol and deionized water used is 2.2 times the weight of the FeSiAl powder particles, and the processing frequency of the ultrasonic cleaning used is 110-130KHz.

[0010] Preferably, in step S1, the passivation treatment is: according to the mass proportion, 100 parts of clean FeSiAl powder particles are placed into 120 parts of a solution consisting of 12 parts of acetone, 0.3 parts of phosphoric acid and 87.7 parts of deionized water for passivation treatment, stirred for 100 minutes, and then dried to obtain FeSiAl powder after the passivation treatment.

[0011] By adopting the above technical scheme, a phosphate passivation corrosion-resistant layer can be formed on the surface of the FeSiAl powder particles by placing clean FeSiAl powder particles in a solution composed of acetone, phosphoric acid and deionized water for passivation treatment. This passivation layer can effectively prevent the oxidation and corrosion of the FeSiAl powder particles in the subsequent process and improve its corrosion resistance. At the same time, due to the presence of the passivation layer, the surface energy of the FeSiAl powder particles can be reduced, which is beneficial to the coating of the silicon dioxide layer in the subsequent in-situ reaction process. In the preparation method of the present application, the passivation treatment is combined with the in-situ reaction to form a synergistic effect. First, a phosphate passivation corrosion-resistant layer is formed on the surface of the FeSiAl powder particles through passivation treatment, and then in the in-situ reaction process, phosphoric acid is used as a catalyst, so that the reaction precursor is hydrolyzed and condensed on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating layer of silicon dioxide. In this way, a composition transition zone is formed between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer, which not only ensures that the coated FeSiAl powder has excellent corrosion resistance, but also has the advantages of small magnetic loss, high effective magnetic permeability, stable performance, long service life, etc. In addition, in the later deformation process caused by external force, the surface protective layer and the FeSiAl powder particles are deformed in coordination, and the possibility of cracks or defects in the silicon dioxide layer is small, thereby obtaining high-reliability powder for molded inductors to meet the needs of the high-end market.

[0012] Preferably, in step S2, the mass ratio of the reaction precursor, phosphoric acid and solvent is 19:3:50-55.

[0013] By adopting the above technical solution, the reaction precursor: the reaction precursor is a key component for generating the surface coating layer. The amount of reaction precursor added directly affects the thickness and quality of the coating layer. By adjusting the amount of reaction precursor added, the thickness of the coating layer can be controlled, thereby affecting the performance of the powder for molded inductors. Phosphoric acid in this application can be used as both a reactant and a catalyst. As a reactant, phosphoric acid reacts with the phosphate passivation corrosion-resistant layer to generate an intermediate transition layer, thereby enhancing the bonding force between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer. As a catalyst, phosphoric acid can accelerate the hydrolysis reaction rate of the reaction precursor and improve the formation efficiency of the coating layer. In addition, phosphoric acid can also form a component transition zone between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer, which helps to improve the corrosion resistance, low magnetic loss, high effective magnetic permeability, stable performance and long service life of the coated FeSiAl powder. The solvent is used to dissolve the reaction precursor and phosphoric acid so that they can be fully mixed and dissolved. At the same time, the solvent can also adjust the viscosity and fluidity of the reaction system, which is beneficial to the uniform distribution and mass transfer process of the reactants. In addition, the solvent can also affect the reaction rate and the structure of the product to a certain extent. In summary, the mass ratio of the reaction precursor, phosphoric acid and solvent is 19:3:50-55, and they have a synergistic effect and jointly affect the preparation process and performance of the powder for molded inductors.

[0014] Preferably, in step S2, the reaction precursor is composed of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a mass ratio of 3:3:4.

[0015] By adopting the above technical scheme, tetraethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane are hydrolyzed, polycondensed and form a uniform in-situ coating layer of silica on the surface of FeSiAl powder particles under the catalysis of a catalyst. This coating layer can effectively protect the FeSiAl powder particles from erosion by the external environment and improve its corrosion resistance. The synergistic effect between tetraethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane can hydrolyze, polycondense and form a uniform and dense in-situ coating layer of nano-silica on the surface of FeSiAl powder particles at a high speed. This coating layer can not only improve the corrosion resistance of FeSiAl powder, but also reduce magnetic loss, increase effective magnetic permeability, and make FeSiAl powder have excellent performance stability and service life. In the later deformation process caused by external force, the surface protective layer and the FeSiAl powder particles are deformed in coordination, and the possibility of cracks or defects in the silica layer is small. This helps to improve the reliability of powder materials for molded inductors and meet the needs of the high-end market. In summary, the reaction precursor is composed of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a mass ratio of 3:3:4, which plays a role in improving the corrosion resistance of FeSiAl powder, reducing magnetic loss, increasing effective magnetic permeability, ensuring performance stability and service life, and improving the reliability of powder for molded inductors in the present application.

[0016] Preferably, in step S2, the solvent consists of ethanol and isopropanol in a mass ratio of 4:3.

[0017] Preferably, in step S3, the catalyst in the solution containing the catalyst is at least one of arginine and lysine, and the solution containing the catalyst uses ultrapure water as a solvent, and its mass percentage concentration is 25%.

[0018] Preferably, in step S3, the process conditions of vacuum drying are: drying at a temperature of 80°C-100°C for 10-12h.

[0019] In a second aspect, the present application provides a powder material for a molded inductor, which adopts the following technical solution: As a general technical concept, the present application also provides a molded inductor powder obtained by the above-mentioned method for preparing a molded inductor powder.

[0020] In summary, the beneficial technical effects of this application are: 1. Improve corrosion resistance: By passivating the FeSiAl powder particles and forming a phosphate passivation corrosion-resistant layer on the surface, the corrosion resistance of the FeSiAl powder can be significantly improved. At the same time, a silicon dioxide coating layer is grown on the surface of the phosphate passivation corrosion-resistant layer through an in-situ reaction, further enhancing its corrosion resistance.

[0021] 2. Reduce magnetic loss: Since a uniform and dense nano-silicon dioxide in-situ coating layer is formed on the surface of FeSiAl powder particles, the magnetic loss can be effectively reduced and the effective magnetic permeability can be improved.

[0022] 3. Improve stability and service life: By optimizing the ratio of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane and the synergistic effect between them, a uniform and dense nano-silicon dioxide in-situ coating layer can be formed on the surface of FeSiAl powder particles, thereby improving the stability and service life of FeSiAl powder.

[0023] 4. High reliability: Since the surface protection layer and the FeSiAl powder particles are deformed in coordination, the possibility of cracks or defects in the silicon dioxide layer is small, so high-reliability powder for molded inductors can be obtained to meet the needs of the high-end market.

[0024] 5. Environmentally friendly: This application uses anhydrous ethanol solution and deionized water for ultrasonic cleaning, avoiding the use of organic solvents and reducing environmental pollution. At the same time, by adding phosphoric acid as a catalyst, waste resource utilization is achieved. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] In the following examples, 1 portion means 10 g.

[0027] Embodiment 1: A method for preparing powder for molded inductors, comprising the following steps: S1. After FeSiAl powder particles with an average particle size of 5.0 μm were ultrasonically cleaned with anhydrous ethanol solution for 30 minutes, they were ultrasonically cleaned with deionized water for 4 times, each cleaning time was 3 minutes, the amount of anhydrous ethanol and deionized water used were 2.2 times the weight of the FeSiAl powder particles, and the ultrasonic cleaning treatment frequency used was 110 KHz; the deionized water was filtered to obtain clean FeSiAl powder particles, and then the clean FeSiAl powder particles were passivated, and the passivation treatment was as follows: according to the mass fraction, 100 parts of clean FeSiAl powder particles were placed in 120 parts of a solution consisting of 12 parts of acetone, 0.3 parts of phosphoric acid and 87.7 parts of deionized water for passivation treatment, stirred for 100 minutes, and dried to obtain FeSiAl powder after passivation treatment; S2. Dissolve 19 parts of a reaction precursor and 3 parts of phosphoric acid in 50 parts of a solvent in advance according to their weight ratio to prepare a mixed solution for generating a surface coating layer, wherein the reaction precursor is composed of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a weight ratio of 3:3:4, and the solvent is composed of ethanol and isopropanol in a weight ratio of 4:3; S3. According to the mass proportions, add 60 parts of passivated FeSiAl powder into 35 parts of pure water and stir evenly to obtain a mixed solution A. Subsequently, add 0.2 parts of an ultrapure aqueous solution containing arginine and lysine catalysts with a mass percentage concentration of 25% to the mixed solution A, stir evenly, heat to 60°C, slowly add 75 parts of the prepared mixed solution, stir to react for 5 hours, and then let it stand for 18 hours to allow the reaction precursor to hydrolyze and condense on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating of silicon dioxide. Then, separate the solid and liquid, wash, and vacuum dry at 80°C for 12 hours to obtain a powder for molded inductors.

[0028] Embodiment 2: A method for preparing powder for molded inductors, comprising the following steps: S1. After FeSiAl powder particles with an average particle size of 20.0 μm were ultrasonically cleaned with anhydrous ethanol solution for 70 minutes, they were ultrasonically cleaned with deionized water for 4 times, each cleaning time was 5 minutes, the amount of anhydrous ethanol and deionized water used was 2.2 times the weight of the FeSiAl powder particles, and the ultrasonic cleaning treatment frequency used was 130KHz; the deionized water was filtered to obtain clean FeSiAl powder particles, and then the clean FeSiAl powder particles were passivated, and the passivation treatment was as follows: according to the mass fraction, 100 parts of clean FeSiAl powder particles were placed in 120 parts of a solution consisting of 12 parts of acetone, 0.3 parts of phosphoric acid and 87.7 parts of deionized water for passivation treatment, stirred for 100 minutes, and dried to obtain FeSiAl powder after passivation treatment; S2. Dissolve 19 parts of a reaction precursor and 3 parts of phosphoric acid in 55 parts of a solvent in advance according to their weight ratio to prepare a mixed solution for generating a surface coating layer, wherein the reaction precursor is composed of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a weight ratio of 3:3:4, and the solvent is composed of ethanol and isopropanol in a weight ratio of 4:3; S3. According to the mass proportions, add 60 parts of passivated FeSiAl powder into 35 parts of pure water and stir evenly to obtain a mixed solution A. Subsequently, add 0.3 parts of an ultrapure aqueous solution containing arginine and lysine catalysts with a mass percentage concentration of 25% to the mixed solution A, stir evenly, heat to 70°C, slowly add 75 parts of the prepared mixed solution, stir the reaction for 4 hours, and then let it stand for 20 hours to allow the reaction precursor to hydrolyze and condense on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating of silicon dioxide; then separate the solid and liquid, wash, and vacuum dry at a temperature of 100°C for 10 hours to obtain a powder for molded inductors.

[0029] Embodiment 3: A method for preparing powder for molded inductors, comprising the following steps: S1. After FeSiAl powder particles with an average particle size of 10.0 μm were ultrasonically cleaned with anhydrous ethanol solution for 50 minutes, they were ultrasonically cleaned with deionized water for 4 times, each cleaning time was 4 minutes, the amount of anhydrous ethanol and deionized water used was 2.2 times the weight of the FeSiAl powder particles, and the ultrasonic cleaning treatment frequency used was 120 KHz; the deionized water was filtered to obtain clean FeSiAl powder particles, and then the clean FeSiAl powder particles were passivated, and the passivation treatment was as follows: according to the mass fraction, 100 parts of clean FeSiAl powder particles were placed in 120 parts of a solution consisting of 12 parts of acetone, 0.3 parts of phosphoric acid and 87.7 parts of deionized water for passivation treatment, stirred for 100 minutes, and dried to obtain FeSiAl powder after passivation treatment; S2. Dissolve 19 parts of a reaction precursor and 3 parts of phosphoric acid in 53 parts of a solvent in advance according to their weight ratio to prepare a mixed solution for generating a surface coating layer, wherein the reaction precursor is composed of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a weight ratio of 3:3:4, and the solvent is composed of ethanol and isopropanol in a weight ratio of 4:3; S3. According to the mass proportions, add 60 parts of passivated FeSiAl powder into 35 parts of pure water and stir evenly to obtain a mixed solution A. Subsequently, add 0.25 parts of an ultrapure aqueous solution containing arginine and lysine catalysts with a mass percentage concentration of 25% to the mixed solution A, stir evenly, heat to 65°C, slowly add 75 parts of the prepared mixed solution, stir the reaction for 4.5 hours, and then let it stand for 19 hours to allow the reaction precursor to hydrolyze and condense on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating of silicon dioxide; then separate the solid and liquid, wash, and vacuum dry at 90°C for 11 hours to obtain a powder for molded inductors.

[0030] Comparative Example 1 The same as Example 3, except that in step S1, the clean FeSiAl powder particles are not passivated.

[0031] Comparative Example 2 The same as Example 3, except that the coating treatment of step S2 and step S3 is not performed.

[0032] Comparative Example 3 The same as Example 3, except that in step S2, the amount of phosphoric acid added is 0 parts.

[0033] Comparative Example 4 The same as Example 3, except that in step S2, the reaction precursor is tetraethyl orthosilicate.

[0034] Comparative Example 5 The same as Example 3, except that in step S2, the reaction precursor is butyltrimethoxysilane.

[0035] Comparative Example 6 The same as Example 3, except that in step S2, the reaction precursor is tetrabutoxysilane.

[0036] Performance Testing The molded inductor powders prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were sampled and tested as follows. The test results are shown in Table 1: Corrosion resistance: The corrosion potential and corrosion current density of the samples were tested using a Princeton Applied Research 273A electrochemical workstation with 3.5wt% sodium chloride solution as the electrolyte. The molded inductors obtained in Examples 1 to 3 and Comparative Examples 1 to 6 were pressed into magnetic rings of 10.73 mm*6.00 mm*3.00 mm using powder materials, and the effective magnetic permeability μ was tested. e (100kHz) and magnetic loss Pcv10mT / 100kHz).

[0037] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The molded inductor powders prepared in Examples 1 to 3 have excellent corrosion resistance, low magnetic loss, high effective magnetic permeability, stable performance, and long service life. In addition, during the later deformation process caused by external force, the surface protective layer and the FeSiAl powder particles are deformed in coordination, and the possibility of cracks or defects in the silicon dioxide layer is small, thereby obtaining a high-reliability molded inductor powder to meet the needs of the high-end market.

[0038] 2) The performance comparison analysis of the powder materials for molded inductors prepared in combination with Example 3 and Comparative Examples 1-2 shows that the corrosion resistance of FeSiAl powder can be significantly improved by passivating the FeSiAl powder particles and forming a phosphate passivation corrosion-resistant layer on the surface. At the same time, a silicon dioxide coating layer is grown on the surface of the phosphate passivation corrosion-resistant layer through an in-situ reaction, further enhancing its corrosion resistance. This double-layer protection can significantly improve the corrosion resistance of FeSiAl powder, while having low magnetic loss, high effective magnetic permeability, stable performance, and long service life.

[0039] 3) The performance comparison analysis of the molded inductor powder obtained in combination with Example 3 and Comparative Example 3 shows that phosphoric acid is added to the in-situ reaction system, so that there is a composition transition zone between the phosphate passivation corrosion-resistant layer and the silicon dioxide coating layer, which not only ensures that the coated FeSiAl powder has excellent corrosion resistance, but also has small magnetic loss, high effective magnetic permeability, stable performance and long service life; and in the later deformation process caused by external force, the surface protective layer and the FeSiAl powder particles are deformed in coordination, and the possibility of cracks or defects in the silicon dioxide layer is small, thereby obtaining a high-reliability molded inductor powder to meet the needs of the high-end market.

[0040] 4) The performance comparison analysis of the powder for molded inductors prepared in combination with Example 3 and Comparative Examples 4-6 shows that the reaction precursor is composed of tetraethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a mass ratio of 3:3:4, and tetraethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane are hydrolyzed and polycondensed on the surface of FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating layer of silicon dioxide. This coating layer can effectively protect the FeSiAl powder particles from erosion by the external environment and improve its corrosion resistance. There is a synergistic effect between tetraethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane, which can hydrolyze and polycondense on the surface of FeSiAl powder particles at a high speed to form a uniform and dense in-situ coating layer of nano-silicon dioxide. This coating layer can not only improve the corrosion resistance of FeSiAl powder, but also reduce magnetic loss, improve effective magnetic permeability, and make FeSiAl powder have excellent performance stability and service life. In the later deformation process caused by external forces, the surface protection layer and FeSiAl powder particles deform in coordination, and the possibility of cracks or defects in the silicon dioxide layer is small. This helps to improve the reliability of powder materials for molded inductors and meet the needs of the high-end market.

[0041] The above embodiments are only used to explain the technical solution of the present application rather than to limit it. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing powder for molded inductors, characterized in that: The following steps are involved: S1, ultrasonically cleaning FeSiAl powder particles with an anhydrous ethanol solution, ultrasonically cleaning with deionized water, filtering the deionized water to obtain clean FeSiAl powder particles, and then passivating the clean FeSiAl powder particles to obtain passivated FeSiAl powder; S2. Preliminarily dissolving appropriate amounts of reaction precursors and phosphoric acid in a solvent according to their mass fractions to prepare a mixed solution for forming a surface coating layer; S3. According to the mass proportion, add 60 parts of passivated FeSiAl powder into 35 parts of pure water and stir evenly to obtain a mixed solution A. Then, drop 0.2-0.3 parts of a solution containing a catalyst into the mixed solution A, stir evenly, heat to 60-70°C, slowly add 75 parts of the prepared mixed solution, stir to react for 4-5 hours, and then let it stand for 18-20 hours to allow the reaction precursor to hydrolyze and condense on the surface of the FeSiAl powder particles under the catalysis of the catalyst to form a uniform in-situ coating of silicon dioxide; then separate the solid and liquid, wash, and vacuum dry to obtain a powder for molded inductors.

2. The method for preparing a powder material for molded inductors according to claim 1, characterized in that: In step S1, the average particle size of the FeSiAl powder particles is 5.0-20.0 μm.

3. The method for preparing a powder material for molded inductors according to claim 1, characterized in that: In step S1, during the FeSiAl powder particle cleaning process, anhydrous ethanol is used for ultrasonic cleaning for 30-70 minutes, and then deionized water is used for ultrasonic cleaning 4 times, each cleaning time is 3-5 minutes, the amount of anhydrous ethanol and deionized water used is 2.2 times the weight of the FeSiAl powder particles, and the processing frequency of the ultrasonic cleaning used is 110-130KHz.

4. The method for preparing a powder material for molded inductors according to claim 1, characterized in that: In step S1, the passivation treatment is as follows: according to the mass fraction, 100 parts of clean FeSiAl powder particles are placed into 120 parts of a solution consisting of 12 parts of acetone, 0.3 parts of phosphoric acid and 87.7 parts of deionized water for passivation treatment, stirred for 100 minutes, and then dried to obtain FeSiAl powder after passivation treatment.

5. The method for preparing powder for molded inductor according to claim 1, characterized in that: In step S2, the mass ratio of the reaction precursor, phosphoric acid and solvent is 19:3:50-55.

6. The method for preparing powder for molded inductor according to claim 1, characterized in that: In step S2, the reaction precursor is composed of ethyl orthosilicate, butyltrimethoxysilane and tetrabutoxysilane in a mass ratio of 3:3:

4.

7. The method for preparing powder for molded inductor according to claim 1, characterized in that: In step S2, the solvent consists of ethanol and isopropanol in a mass ratio of 4:

3.

8. The method for preparing powder for molded inductor according to claim 1, characterized in that: In step S3, the catalyst in the solution containing the catalyst is at least one of arginine and lysine, and the solution containing the catalyst uses ultrapure water as a solvent, and its mass percentage concentration is 25%.

9. The method for preparing powder for molded inductor according to claim 1, characterized in that: In step S3, the process conditions of vacuum drying are: drying at a temperature of 80°C-100°C for 10-12 hours.

10. A powder material for molded inductors, characterized in that: The molded inductor is prepared by the method for preparing a powder material for molded inductor according to any one of claims 1 to 9.